ANALISIS DAYA SAING KEDELAI TERHADAP TANAMAN PADI DAN JAGUNG - Rininta Saraswati; Salyo Sutrisno; T. Adisarwanto (BUANA SAINS, 2011)
In general soybean area is the same area of rice or maize, and in fact there were competitive between each crop. The aims of the study is to evaluate competitiveness of soybean with rice and maize. Survey methodology was applied with farmer respondent of soybean from two village namely Karanghardjo and Panunggalan , Sub District Pulokulon, Grobongan District during October 2008 to Februari 2009. Farm analysis, Equalibrium analysisi and Competitiveness was used in this study. The result showed that soybean still competitive if minimal productivity of soybean reach minimum > 1.90 t/ha and > 1.80 t/ha respectively to rice and maize with the minimum price of soybean Rp. 4.500/kg